Meating of the Minds: Who Denies Animal Mind in Response to the Meat Paradox? - Nicholas P. Tan; Brock B. Bastian; Luke D. Smillie (Psychology of Human-Animal Intergroup Relations)
Most people abhor animal cruelty but choose to eat meat. To resolve feelings of conflict associated with this so-called “meat paradox”, meat-eaters appear to downplay the capacity of animals to think and feel. However, the strength of animal mind denial seems likely to vary between individuals—according to one’s concern for animal welfare or enjoyment of meat, for instance. Across two pre-registered studies (S1: N = 355, S2: N = 251), we examined personality traits, attitudes, and beliefs that may predict the strength of animal mind denial in relation to the meat paradox. Results suggest that those lower in openness/intellect or emotion regulation ability, or higher in meat-commitment, deny animal mind more strongly when reminded of the link between meat eating and animal suffering. We discuss the degree to which these findings align with dissonance-based explanations for animal mind-denial in response to the meat-paradox.